Customers’ heterogeneity and store patronage intention: a study of department stores in Libya / Iman Elsalehin Bouthahab - Bouthahab, Iman Elsalehin (Institute of Graduate Studies, UiTM, 2013)
The retail industry of Libya has only recently been developed by private and public investments and as such, many stores including department stores are still in the initial stage of development. Libyan customers now have many options to which stores they will visit, but do they have the intent to visit their stores especially when Libyan customers have unique characteristics that might affect their intention to visit the new retailers in Libya? Therefore, the main purpose of this study is to investigate whether customers‘ heterogeneity is able to explain customers’ patronage intention to department stores in Libya. The results can assist the Libyan retailers especially department stores when changing their marketing strategies for the Libyan market. Namely this study will help retailers and investors to understand Libyan customers‘ heterogeneity and their behaviors so that they can develop their retail strategies better. In addition, an understanding of patronage is a crucial issue for managers because it helps them to determine the intention of those customers who have the most intention to buy from them…